Monkey Pox: Virology, Epidemiology, Vaccines, and Therapeutic Approaches - Geevarghese, Abin V. (Anti-Infective Agents, 2024)
The monkeypox virus, which was historically common in West and Central Africa, is the source of the zoonotic disease known as monkeypox. Instances, however, have recently been confirmed in a few non-endemic nations outside of Africa. In light of the COVID-19 pandemic, the WHO labeled the current monkeypox epidemic a public health emergency of global concern on July 23, 2022. The international society may be in jeopardy due to the rapidly increasing number of confirmed cases. Current epidemiological statistics indicate that the high frequency of transmission from person to person might result in additional epidemics, especially among guys who have sex with males. Despite certain therapeutic benefits of already prescribed pharmaceuticals, there is an urgent need for the creation of antiviral therapies and vaccinations to ward off the monkeypox virus. I offer pertinent information to help people understand the monkeypox virus and help medical professionals in stopping the spread of the monkeypox virus.
Keywords: virology